Experiences of undergraduate nursing students who worked clinically during the COVID‐19 pandemic. Issue 1 (21st July 2022) - Dempsey, Laura; Gaffney, Lorraine; Bracken, Sinead; Tully, Agnes; Corcoran, Olivia; McDonnell‐Naughton, Mary; Sweeney, Lisa; McDonnell, Denise
Abstract: Aim: This study explored the experiences of undergraduate nursing students who worked clinically during the COVID‐19 pandemic in Irish healthcare settings. Design: A qualitative descriptive approach was employed. Methods: Online focus group interviews were used to collect data from general nursing students ( N  = 47) between February and April 2021. Data were analysed using thematic analysis. Results: Descriptive thematic analysis of the data revealed five themes; changes in care delivery, changes in communication and relationships with the patient, an emotionally charged work atmosphere, coping strategies during the pandemic and student learning specific to COVID‐19. Challenges such as an increased workload, fear of contracting the virus and taking on novel and additional roles were revealed. Students remained undeterred, and despite the many challenges faced, they largely viewed their experiences as a source of personal and professional growth, and benefitted from the learning opportunities afforded to them.